2020
DOI: 10.3389/fcell.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Dysfunction and Exhaustion in Cancer

Abstract: Tumor immunotherapy is a promising therapeutic strategy for patients with advanced cancers. T cells are key mediators of antitumor function that specifically recognize and react to tumor-expressing antigens and have proven critical for cancer immunotherapy. However, T cells are not as effective against cancer as expected. This is partly because T cells enter a dysfunctional or exhausted state, which is characterized by sustained expression of inhibitory receptors and a transcriptional state distinct from that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
226
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(232 citation statements)
references
References 118 publications
3
226
0
3
Order By: Relevance
“…Tumor immunotherapy is a promising and transformative therapeutic strategy for patients with advanced cancers [26,27]. Our data also demonstrated that NRF1 expression correlated with the in ltration status of B cells, CD4 + and CD8 + T cells, macrophages, neutrophils, and DCs.…”
Section: Discussionsupporting
confidence: 68%
“…Tumor immunotherapy is a promising and transformative therapeutic strategy for patients with advanced cancers [26,27]. Our data also demonstrated that NRF1 expression correlated with the in ltration status of B cells, CD4 + and CD8 + T cells, macrophages, neutrophils, and DCs.…”
Section: Discussionsupporting
confidence: 68%
“…The tumor microenvironment is highly heterogenous with the TILs constituting the vast majority of immune infiltrates. 33 The chronic exposure of cancer antigen to the memory T cells could alter their differentiation and activation, leading to exhaustion. 34 It has been reported that T-cell exhaustion is initiated in early stages after the onset of tumor in preclinical tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CRTH2 and ST2 expression was more upregulated in PD-1 high ILC2s than in PD-1 low ILC2s. Since an inhibitory factor in later stages, similar to cytotoxic T cells (32). Indeed, a previous study demonstrated that PD-1 expression on ILC2s was upregulated after ILC2 activation by IL-33 in obese mice (40).…”
Section: Discussionmentioning
confidence: 99%